PENGUJIAN REFRIGERAN ALTERNATIF RAMAH LINGKUNGAN PADA MESIN PENDINGIN JENIS KOMPRESI UAP - Widagdo, Tri (Politeknik Negeri Sriwijaya, Indonesia, 2010)
The Vapor Compretion Refrigeration Machine is very commonly used, either for home or industuial scale. The pefomance of machine is depend on the quality of the fluid (refigerant) that operated. The refrigerant that usally used is R-12 that have very good thrmoynamic properties. In fact this refrigerant came from the CFC’s (Chlorofluoride Carbonate), is the substance which have potency to detruct the inviromenthal system. From that writer tend to do research that concern with same alternative refrigrerant. They are R-134, Butana and Petrozon. The perfomance that result from machine than compared with the perfomance of refrigeration machine that operatet with R-12 refrigerant. Research activity begun with instaling refigerant machine complatet with experimanthal divice and control system. Using the R-12 refrigerant, the maximum COP is 2.21. The COP of refrigeration machine that operated with alteranative refrigerant are: 1. For Butana the maximum COP is 2.1 at low cooling load and evaporator pressure 2.6 bar 2. For R-134a the maximum COP is 2.4 at high cooling load and evaporator pressure 1.2 bar 3. For Petrozon the maximum COP is 2.2 at high cooling load and evaporator pressure 2.6 bar